Gas Geochemistry of the Ordovician–Carboniferous Sediments in Well A1-NC175, Ghadames Basin, NW Libya - Osama Rahil Shaltami; Abdullah Yousuf Altarhouni; Mustafa A. Ben Hkoma (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
The authors evaluated the geochemical characteristics of source rock and natural gas of the Ordovician–Carboniferous strata in well A1-NC175, Ghadames Basin, NW Libya. In terms of the source rock geochemistry, the organic richness ranged from poor to good. The predominant kerogen was of type III and IV. There were three levels of thermal maturity: early, peak, and late. The shales mainly contained indigenous hydrocarbons. The shales may be regarded as oil and/or gas sources. The shales are not considered a potential reservoir for extracting unconventional hydrocarbons. In terms of the gas geochemistry, thermogenic gases predominated in the samples. The gasses were wet in nature.